Analisis Pelaksanaan Rekrutmen Pegawai Instalasi Gawat Darurat Pada Masa Pendemi Corona Virus Desease 19 di Rumah Sakit Umum Bayung Lencir - Pharsy, Muhammad Daniel; Idris, Umiyati; Asteriniah, Femi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
This study aims to analyze the Implementation of the Recruitment of Emergency Installation Employees during the Corona Virus Disease 19 Pandemic at the Bayung Lencir Regional General Hospital. by using a qualitative descriptive approach. This study uses an instrument consisting of interviews with research informants, observations and literature studies. The data used in this study consisted of qualitative data and quantitative data sourced from primary and secondary data. The data were analyzed through the following stages: sorting, analysis/discussion, and drawing conclusions. From the results of the study, it is known that employee recruitment is seen from the stages of submitting additional proposals, it is known that the process of finding job information has obstacles in the form of difficulty in coordination in order to search for job information carried out by team members, this condition is because during the pandemic must comply with health protocols and remote coordination with team members running wfh was a bit of a problem. The selection of the recruitment method is done by online interview, this method still has problems where if the network conditions are not stable then the interview process is hampered. Approval of proposals is carried out at a selection team meeting and decisions are taken jointly by looking at the conditions and types of positions needed for the procurement of employee recruitment. Judging from the selection stages of prospective employees, it is known that the administrative selection process contains requirements that have been announced to prospective applicants. The implementation of employee selection has been carried out in accordance with the recruitment procedures that have been determined. At this stage it is felt that there are still weaknesses where the selection team cannot see directly the competence of employees, if the network is in an unstable condition, interviews are conducted intermittently. Remote interviews or online interviews using an internet connection experience power outages, both experienced by hospital interviewers and prospective employees. In addition, the internet connectivity owned by prospective employees is often not as good as the connection at the hospital so that it can reduce the effectiveness of conducting interviews. Judging from the stages of employee acceptance, it is known that it has been running according to the implementation guidelines.